Green synthesis of NiO nanoparticles with activated carbon from Ficus carica leaf and extract for malachite green removal - Hadi, Raghad Mohammed; Salman, Sami D. (Iraqi Journal of Chemical and Petroleum Engineering, 2025)
The green synthesis of nanoparticles and activated carbon has attracted researchers’ interest due to its rapid, cost-effective, sustainable, and environmentally friendly nature. In this paper, the synthesis of activated carbon (AC) and nickel oxide nanoparticles (NiO-NPs) from Ficus carica leaf and their extracts for the removal of malachite green from aqueous solutions. activated carbon (AC) was synthesized from Ficus carica leaves using a pyro-carbonic acid microwave method. In contrast, nickel oxide nanoparticles were produced using leaf extracts as a reducing and stabilizing agent. The manufactured activated carbon and NiO nanoparticles were characterized by Brunauer-Emmett-Teller analysis, scanning electron microscopy with energy-dispersive X-ray spectroscopy, X-ray diffraction, and Fourier transform infrared spectroscopy. The influence of various factors, including malachite green concentration, pH, contact time, and dosages of NiO, AC, and NiO/AC, was examined using Response Surface Methodology (RSM) in Design-Expert (13 Stat-Ease). the optimal parameters for achieving maximum removal efficiency of malachite green dye were determined to be an initial concentration of 150 mg/L, pH of 4, a contact period of 120 minutes, and an adsorbent dosage of 0.25 g/L, resulting in removal efficiencies of 97.9202%, 98.8932%, and 99.9776%, respectively. The equilibrium adsorption data were analyzed using the Langmuir, Freundlich, and pseudo-first- and second-order kinetic models. the results indicated that the Freundlich isotherm and pseudo-second-order kinetic models were the most effective in representing the equilibrium adsorption data.